Studi Profil Penggunaan Bahan Alam dan Sediaan Peningkat Imunitas Tubuh pada Mahasiswa Politeknik Sandi Karsa - H. Ambo Lau, Sulfiyana; Indes Fitya (Jurnal Farmasi Sandi Karsa, 2023)
Body immunity is an immune system designed to detect or destroy foreign objects that enter the body to avoid disease. Immunity is important to maintain so that the body remains healthy, one way is by consuming natural ingredients or preparations to increase body immunity. The purpose of this study was to determine the profile study of the use of natural materials and immune-enhancing preparations in Politeknik Sandi Karsa students. This type of research uses a descriptive method, namely research that includes surveys with data collection in the form of questionnaires with a total of 69 respondents. The sampling method uses Non Probability Sampling with Purposive Sampling techniques using questionnaires using the Opened Questionare questionnaire format in data collection and report recording. The results of this study show that there are still students who use natural ingredients in the form of ginger, lemongrass, honey, ginger, moringa leaves, turmeric and life connection leaves while the body's immunity-enhancing preparations are used such as vitamin C, immunos, stimuno, imboost force, vit Bcom-Z and Bcom and reject wind. So it can be concluded that the Profile Study of the Use of Natural Ingredients and Immune Enhancing Preparations in Sandi Karsa Polytechnic Students who use natural ingredients in the form of ginger is 20 respondents (29.00%) and immune boosting preparations using vitamin C are 19 respondents (27.55%).